Analisis Faktor-Faktor yang Memengaruhi Tingkat Non-Performing Financing (NPF) di Bank Umum Syariah Indonesia Periode 2015-2021 - Syahrifa Dwi Fitri; Jaka Sriyana (SAFE-Network, 2023)
The development of Islamic banking in Indonesia continues to increase. The Islamic banking industry has a bright future, one of which is supported by most of the Indonesian people who are Muslims so that the market share they have is also large. To maintain its existence, of course, Islamic banking must maintain the trust given by the community to collect and distribute funds back to the community. This study aims to examine the factors that influence the level of Non-performing Financing (NPF) in Islamic Commercial Banks, because the higher the NPF of a bank indicates poor or unhealthy banking performance. This research data is secondary data obtained from the Islamic Banking Statistics (SPS) report on the page of the Financial Services Authority (OJK). The analytical method used is the Vector Error Correction Model (VECM) with the help of an analytical tool, namely E-views.10. The results of this study indicate that in the short term the only significant variable is the NPF variable itself. While in the long term the ASSET variable has a negative and significant effect, the CAR variable has a positive and significant effect on the NPF in BUS. Then, FDR and BOPO have no effect in the long term or in the short term.